Case report: Intralesional secukinumab injection for pediatric nail psoriasis: does it have to be a positive outcome? - Wang, Xuesong; Sun, Yonghu; Xie, Weixing; Liu, Hong; Liu, Guoyan (Frontiers in Immunology, 2024)
Recent studies have shown that local injection of sSecukinumab can achieve positive therapeutic effects when applied in the treatment of nail psoriasis. At present, there have been no other studies on the use of biological agents in the treatment of pediatric nail psoriasis. Three children were included in the study to evaluate the efficacy and safety of periungual injection and long-term injection of sSecukinumab in the treatment of nail psoriasis in children. It was found that local injection did not achieve a remarkablesignificant therapeutic effect. The nail lesions were improved continuously by subcutaneous injection once a month.